Analysis the Application of the Weighted Product Method in Decision Support Systems for Assistance Programmes for MSMEs - Berno Doduk, Thomas Aquino; Supriyanto, Heri; Al Hafidz, Mohammad; Prasetya, Muhammad Septama; Karyawan, Moch Anang (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
Productive Micro Business Assistance (BPUM) is a government policy. This assistance has been carried out since the Covid-19 Pandemic in Indonesia. The Mojokerto city government conducts a selection of MSMEs which is expected to avoid errors in determining MSME assistance. Therefore, a decision support system is needed that is developed using the Weighted Product method to make it easier and faster to determine MSMEs that are eligible to receive assistance. The stages of system development start from problem analysis, data collection, analysis of method application, and system development. Based on the calculation of the resulting S vector, the largest value is 0.10568 and the smallest value is 0.05886 from 9382 MSME data. The last calculation is the V vector value which produces recommendations in the form of data ranking that can be used by the Mojokerto City Diskopukmperindag to determine which MSMEs are entitled to receive assistance. The results of the selected alternatives are in accordance with the ranking with the largest value of 0.10568 and the smallest value of 0.05886. Providing recommendations by the decision support system to policy makers can be based on the largest relative preference value owned by MSMEs.